Mine! - Crum, Shutta (Knopf, 2011)
"Crum uses only the title word (if you don't count a single "Woof?"), but the various inflections speak volumes about the comic dynamics of sharing...[Barton's] dizzyingly expressive digitized pencil sketches seem to be everywhere at once continually reframing the action to make sure readers savor every gleefully anarchic moment."--Publishers weekly, starred review